CONTENT EVALUATION OF INSTAGRAM POSTS RELATED TO FOOD AND HEALTH PRODUCED BY DIGITAL INFLUENCERS - Pergher, Gabriela; Vaz, Rosangela; Werner, Marina (Seven Editora, 2024)
With the growth of social networks, influencers have a great impact on the eating habits of their followers, promoting products and diets without scientific basis. The present study evaluated the content of Instagram® posts  related to food and health, produced by digital influencers without a qualification in nutrition. The methodology used was descriptive, exploratory and analytical, with a qualitative approach, analyzing five influencer profiles between March 2023 and September 2024. The publications were categorized into "Dissemination of sponsored products" and "Guidelines on what to eat". The results showed that influencers encourage the practice of exercise and the consumption of products, without considering nutritional individuality and health risks. It is concluded that the guidance of these digital influencers can have a negative impact on the physical and mental health of their followers, reinforcing the need for qualified professionals to provide nutritional guidance. DOI:https://doi.org/10.56238/sevened2024.037-039